De-Westernization and Indonesia's Hedging Strategy in the Global South Forum: Constructivist and Neorealist Perspectives - Rafiqi, Fathan; maksum, Ali (Andalas Institute of International Studies, 2026)
This article critically examines Indonesia’s hedging strategy amid the ongoing transformation of the global order, focusing particularly on its engagement with Global South platforms such as BRICS+, the Non-Aligned Movement, and South-South cooperation forums. Adopting an integrated theoretical approach that combines constructivist and neorealist perspectives, the study investigates how Indonesia simultaneously projects a postcolonial, pluralist identity while engaging in pragmatic alignments with both Western and non-Western powers. The research employs critical discourse analysis to assess official diplomatic statements, policy texts, and multilateral positioning, uncovering a hybrid diplomatic strategy characterized by normative performance and structural adaptability. Indonesia’s ambidextrous behavior balancing identity-based commitments with strategic flexibility exemplifies the complex navigation of middle powers in a multipolar, post-hegemonic era. This dual logic reflects not only Indonesia’s historical legacies and normative aspirations but also its calculated efforts to buffer against systemic uncertainty and preserve foreign policy autonomy. The study offers a novel theoretical synthesis by bridging ideational and materialist analyses to explain Indonesia’s diplomatic conduct within a reconfiguring global architecture. In doing so, it contributes to broader debates on middle-power diplomacy, Global South agency, and the epistemic diversification of international relations theory, while offering empirically grounded insights into the evolving role of non-Western actors in global governance reform.